Synthesis and Biological Activity of Piperidinothiosemicarbazones Derived from Aminoazinecarbonitriles - Dagmara Ziembicka; Katarzyna Gobis; Małgorzata Szczesio; Ewa Augustynowicz-Kopeć; Agnieszka Głogowska; Izabela Korona-Głowniak; Krzysztof Bojanowski (Pharmaceuticals, 2023)
To investigate how structural modifications affect tuberculostatic potency, we synthesized seven new piperidinothiosemicrabazone derivatives 8–14, in which three of them had a pyrazine ring replacing the pyridine ring. Derivatives 8–9 and 13–14 exhibited significant activity against the standard strain (minimum inhibitory concentration (MIC) 2–4 μg/mL) and even greater activity against the resistant M. tuberculosis strain (MIC 0.5–4 μg/mL). Additionally, the effects of compounds 8–9 were entirely selective (MIC toward other microorganisms ≥ 1000 μg/mL) and non-toxic (IC50 to HaCaT cells 5.8 to >50 μg/mL). The antimycobacterial activity of pyrazine derivatives 11–12 was negligible (MIC 256 to >500 μg/mL), indicating that replacing the aromatic ring was generally not a promising line of research in this case. The zwitterionic structure of compound 11 was determined using X-ray crystallography. Absorption, distribution, metabolism, and excretion (ADME) calculations showed that all compounds, except 11, could be considered for testing as future drugs. An analysis of the structure–activity relationship was carried out, indicating that the higher basicity of the substituent located at the heteroaromatic ring might be of particular importance for the antituberculous activity of the tested groups of compounds.